PERAN HIPOKSIA PADA PATOGENESIS PENYAKIT GINJAL - Sastrawan, I Gede Pande; Suwitra, Ketut (journal of internal medicine, 2012)
Chronic kidney disease is a current major worldwide health problem with an increasing prevalency. Kidney is a sensitive organ with hypoxic condition relate to its high tubular epithelial cells and vascular oxygen consumption. Chronic peritubular ischemia may occur through several interrelating mechanisms. The activation of local renin-angiotensin system, angiotensin II, could induce hypoxia by means of hemodinamic and nonhemodinamic mechanisms. Anemia in renal disease could accelerate the decline of renal function through the induction of tubulointerstitial hypoxia. Non Steroidal Anti Inflamatory Drugs (NSAID) could evoke renal medullar hypoxia by its regional hypoperfusion mechanism and the escalation of tubular transport. The Outer region of renal medulla and tubulus are main target of hypoxic renal damage. The mechanism of hypoxia induced Acute Kidney Disease involves renal vascular and tubulus through the reduction of blood flow and the increasing of tubular oxygen demands. The Patofisiology of hypoxia induced chronic kidney disease occurs by tubulointerstitial damage which induce fibrogenesis, causing interference of peritubular blood flow and oxygen consumption.
Keywords: Hypoxia, pathogenesis, kydney diseases